B293 Neuraxial anaesthesia in spina bifida occulta: is it works?. (11th August 2022) - Duarte, F; Marques, C; Lucas, P
Abstract : Background and Aims: Women with spina bifida present both obstetrical and anaesthesia challenges. They are more likely to require a caesarian delivery and traditionally neuraxial anesthesia has been avoided due to concerns of worsening neurologic disability. Methods: A 35-year-old G1P0, at 37 weeks' gestation, was proposed to an elective caesarean section because of her spinal bifida occulta medical history. An MRI scan could not be performed before hospital admission. She reported no motor or sensory deficits. At physical exam, we could see a skin dimpling, 3, 5 cm away from the anal margin. Despite we don't have a spinal image, we decided to perform a combined spinal and epidural anaesthesia. With the patient in sitting position, the puncture in L3-L4 epidural level was performed with a Tuohy 18 G needle. The epidural space was located 5 cm deep from the skin. The spinal block was performed with the "needle-through-needle" technique. After clear cerebrospinal fluid flowed, it was administered 8, 5 mg of 0, 5% hyperbaric bupivacaine and 2, 5 µg of sufentanyl in the subarachnoid space. After the injection, an epidural catheter was introduced 9 cm cephalic. Results: The block reached approximately T4 level in about ten minutes after injection, at which point surgery was begun. The surgery lasted about 60 minutes and there was no need to epidural top-up. Conclusions: Administration of epidural or combined spinal and epidural anaesthesia may be considered in women with various forms of spinal dysraphism and stable neurologic function. The complications encountered are related to the altered anatomy.